(untitled) (Advancements in Homeopathic Research, 2023)
In their maiden publication (4) Gupta et. al. demonstrated that majority of patients of chronic renal failure can be improved or at least prevented from further deterioration by homoeopathic treatment along with change in life style, strict diet and regimen along with supportive medicines for controlling diabetes and hypertension. Recently Gupta et. al. published a series of 3 cases on successful management of CRF(11) and proposed to publish further series of best responding cases to update the physicians about successful treatment of renal failure by homoeopathic remedies, thereby avoiding dialysis and renal transplant. This second case series is on management of CRF by Natrum muriaticum selected on the basis of individualization. The first case in this series is a well-diagnosed, non-dialysed case of CKD of a 56-year old hypertensive male with more than 4 years of follow-up. The second case is of a 40-year old female with primary sterility with follow up of 3 years. The third case is of a 53-year old male with hypertensive nephropathy with 3 year follow up. In all the 3 cases, repeated renal function test and eGFR, calculated by equation from the ‘Modification of Diet in Renal Disease’ (MDRD) equation (5) considering the age and creatinine, is considered the main parameter to assess the functional status of kidney and response to homoeopathic treatment.